RISKS AND PROSPECTS OF INVESTING IN CAR SERVICE COMPANIES - Амелина, Наталия (SWorldJournal, 2020)
Introduction. The analysis of the level of fixed income and finding the optimal investment under uncertainty requires a risk minimisation and management control model for the risks arising from the investment activity. The level of investment has a direct